2004
DOI: 10.1111/j.1439-0523.2004.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Cynara cardunculus revealed by AFLP markers: comparison between cultivars and wild types from Sicily*

Abstract: Genetic diversity in 49 plants of 16 accessions representing one wild and two cultivated taxa of Cynara cardunculus L. (wild cardoon, cultivated cardoon and globe artichoke) was investigated using amplified fragment length polymorphic (AFLP) analysis. Four pairs of primers identified a total of 264 scorable loci, 196 of which were polymorphic. The number of markers scored per primer combination ranged from 41 to 107, with an average of 66 markers per primer combination. All the primer combinations detected pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 23 publications
1
28
1
1
Order By: Relevance
“…The present results revealed that the Shannon diversity of E. adenophorum was higher than some plants that reproduce asexually (Keiper and Mcconchie 2000), especially some widely distributed, perennial, triploid and obligate apomictic reproduction plants (Carmen et al 1999), and also some sexually reproducing plants (Raccuia et al 2004). At the species level, our results are consistent with the genetic diversity of another Asteraceae species, in which relatively high genetic variation was related to life history and ecological characteristics, such as a wide geographic distribution and wind-borne seed dispersal mechanisms (O'Hanlon et al 1999).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The present results revealed that the Shannon diversity of E. adenophorum was higher than some plants that reproduce asexually (Keiper and Mcconchie 2000), especially some widely distributed, perennial, triploid and obligate apomictic reproduction plants (Carmen et al 1999), and also some sexually reproducing plants (Raccuia et al 2004). At the species level, our results are consistent with the genetic diversity of another Asteraceae species, in which relatively high genetic variation was related to life history and ecological characteristics, such as a wide geographic distribution and wind-borne seed dispersal mechanisms (O'Hanlon et al 1999).…”
Section: Discussionmentioning
confidence: 51%
“…The amplified fragment length polymorphism (AFLP) analysis is highly reproducible and can be used to detect high levels of polymorphism in a single assay, requiring no prior knowledge of DNA sequences (Vos et al 1995). The genetic diversity of several invasive plant species has been successfully assayed using AFLP markers (O'Hanlon et al 1999;Raccuia et al 2004).…”
mentioning
confidence: 99%
“…In fact, the artichoke seems the most sensitive to salinity stress than the cultivated and wild cardoon. [3] showed a good variability among wild cardoon populations both in salinity resistance and water stress during germination.…”
Section: Discussionmentioning
confidence: 99%
“…It"s allogame and propagated by seeds (achenes), although the germination can occur throughout the year during the good conditions, the growth extends from September (emergence) to July (mature achenes), and the flowers are usually produced by plants of two years [2]. This taxon is fully crosscompatible and interfertile with both the globe artichoke and the cultivated cardoon [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation